Progress in Modeling and Applications of Solid Electrolyte Interphase Layers for Lithium Metal Anodes - Zhicong Wei; Weitao Zheng; Yijuan Li; Shaoming Huang (Nanomaterials)
The increasing demand for high-specific-energy lithium batteries has stimulated extensive research on the lithium metal anode owing to its high specific capacity and low electrode potential. However, the lithium metal will irreversibly react with the electrolyte during the first cycling process, forming an uneven and unstable solid electrolyte interphase (SEI) layer, which results in the non-uniform deposition of Li ions and thus the formation of lithium dendrites. This could cause a battery short circuit, resulting in safety hazards such as thermal runaway. In addition, the continuous rupture and repair of the SEIs during the repeated charge/discharge processes will constantly consume the active lithium, which leads to a significant decrease in battery capacity. An effective strategy to address these challenges is to design and construct ideal artificial SEIs on the surface of the lithium metal anode. This review analyzes and summarizes the mathematical modeling of SEI, the functional characteristics of SEIs with different components, and finally discusses the challenges faced by artificial SEIs in practical applications of lithium metal batteries and future development directions.